Low temperature electron transport on semiconductor surfaces - Lastapis, M.; Riedel, D.; Mayne, A.; Bobrov, K.; Dujardin, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The low temperature electron transport on semiconductor surfaces has been studied using an ultra high vacuum, variable temperature Scanning Tunneling Microscope (STM). The STM I(V)spectroscopy recorded at various temperatures has enabled to investigate the temperature dependence (300 K to 35 K) of the surface conductivity of three different semiconductor surfaces:highly doped n-type Si(100), p-type Si(100), and hydrogenated C(100). Low temperature freezing of specific surface electronic channels on the higly doped n-type Si(100) and moderately doped p-type Si(100) surfaces could be achieved whereas the total surface conductivity on the hydrogenated C(100) surface can be frozen below only 180 K.